Identifying the Cases of Injury Among the Competitive Trampoline Athletes - Kirişci, İlker; Alpkaya, Ufuk (Marmara Üniversitesi, 2019)
This study has been conducted to identify the injuries of the trampoline athletes during training andcompetition, the frequency of injuries with respect to the parts of the body, and the cases like the availabilityof the medical personnel and how a medical intervention is performed. The sample of the study consistsof a total of 59 athletes with the average age of 13.05 years (± 2.58 years), participating in the 2018 TurkishChampionships. To collect data, “Information Form” created by the researchers was used. In analyzing thedata obtained, descriptive statistical analysis (frequency analysis) was used. It was found that 73 % of theathletes had gone through physical evaluations and 62,7% had experienced sports injuries; and furthermore,during the 73 % of these injuries, there had been no medical personnel on site. It was concluded that 89,1 %of the injuries occurred during training. On the other hand, 29,7 % of the injuries occurred due to technicalimpairment, 27 % due to lack of concentration and motivation, 18,9 % due to insufficient warm-up, and10,8 % due to the lack of safety mats. During the first aid, in 86,4 % of the cases a cold compress was applied,whereas in 5,4 % of the cases a hot compress was. 62,2% of the athletes preferred to go to the doctor for thetreatment of their injuries, while 21,6% applied a method recommended by the coach. The most commoninjuries were in the knee (23,7%), foot and ankle (18,6%), elbow-arm (13,5%) hip (8,9%), wrist (6,7%), head– face (10,1%), spine (10,1 %), and neck regions (8,4 %), respectively.

Bu çalışma, trampolin cimnastik sporcularının antrenman ve yarışma sırasındaki yaralanma durumları, vücut bölgelerine göre yaralanma sıklıkları ve yaralanma sırasındaki sağlık personelinin mevcudiyeti gibi durumların tespiti ve nasıl müdahale edildiğini belirlemek için yapılmıştır. Çalışmanın örneklemini, 2018 yılında Türkiye Şampiyonası’na katılan, yaş ortalaması 13,05 yıl (±2,58 yıl) olan toplam 59 sporcu oluşturmuştur. Verilerin toplanmasında araştırmacılar tarafından oluşturulan “Bilgi Formu” kullanılmıştır. Elde edilen verilerin çözümlenmesinde; tanımlayıcı istatistik analiz (frekans analizi) kullanılarak analiz edilmiştir. Sporcuların % 73’ü sağlık kontrolünden geçtiği, % 62,7’sinin spor yaralanmasına maruz kaldığı ek olarak bu yaralanmaların %78,3’ünde ise sağlık personelinin bulunmadığı tespit edilmiştir. Bunun yanı sıra yaralanmaların %89,1’inin antrenmanda meydana geldiği sonucuna ulaşılmıştır. Diğer yandan yaralanmaların %29,7’si teknik bozukluktan kaynaklanırken, %27’si konsantrasyon eksikliği ve motivasyon bozukluğundan meydana geldiği, %18,9’u yetersiz ısınma, %10,8’i ise emniyet minderlerinin olmaması sebebiyle meydana geldiği tespit edilmiştir. İlk müdahale sırasında %86,4 soğuk uygulama yapılırken, %5,4’ünün sıcak uygulama yaptığı tespit edilmiştir. Sporcuların %62,2’si yaralanmaların tedavisi için doktora gitmeyi tercih ederken, %21,6’sı ise antrenörün önerdiği yöntemi uygulamıştır. Yaralanmalar en çok diz bölgesinde (%23,7), ve sırasıyla ayak – ayak bileğinde (%18,6), dirsek-kol (%13,5) kalça (%8,9), el-el bileği (%6,7), baş – yüz (%10,1), Omurga (%10 1), boyun (% 8,4) bölgesinde olduğu görülmüştür.
Yarışmacı Trampolin Sporcularında Yaralanma Durumlarının Belirlenmesi
Keywords: Sports Medicine; Spor Hekimliği